Influence of Fortifying Graded Levels of Moringa oleifera Leaf Powder on Growth Performance and Haematobiochemical Indices of Broiler Chickens - Verma, Ajeet K.; Pramanik, Partha S.; Verma, Manoj K.; Gautam, Sachin; Kumar, Rajesh; Saurabh, (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study was conducted to evaluate the influence of Moringa oleifera leaf powder (MOLP) on the growth and haemato-biochemicalindices of broiler chickens. A total of 250-day-old broiler chicks (Vencobb-430) were randomly distributed into five groups with 5replicates of 10 birds in each. Different dietary treatments were; basal diet with no supplement (NC- negative control) and a basal dietsupplemented with antibiotics (PC-positive control), 1% MOLP (MOLP1), 1.5% MOLP (MOLP1.5), and 2% MOLP (MOLP2). Bodyweightgain (BWG), feed intake (FI), feed conversion ratio (FCR), haemato-biochemical parameters, and economics were assessed in 35 daysof the experiment. The results showed that BWG of birds was significantly (p
Keywords: Broilers; Growth performance; Haemato-biochemical profile; Leaf powder supplement; Moringa oleifera.